Teaching English Through Music: Multimodal Learning Activities for Primary School Children - Shakilla Arzaqi Viandi; Yuna Tresna Wahyuna; Yogi Setia Samsi (Syntax Corporation Indonesia, 2025)
This paper discusses an innovative approach to English language learning for children through the integration of music and songs. The author seeks to understand how music influences students' learning motivation and improves their English language skills. The theory underpinning this research is Gardner's multiple intelligences, which recognizes that each individual has different types of intelligence, including linguistic intelligence. The research also links this theory to multimodality, an approach that utilizes different media or ways of learning to enrich the educational process. Preliminary findings suggest that music can be an effective tool for promoting language skills, provided the methods used are varied and appropriate to the needs of the students.